Viral diseases and the brain: Long COVID puts the spotlight on how viral infections affect the brain. (29th November 2021) - Hunter, Philip
Abstract : Various viruses can affect the brain directly or indirectly. The specter of Long COVID has focused research on how respiratory viruses can cause infection and inflammation of brain cells.